Relationship of the firm with plant organ with aggressiveness oh Phytophthora capsici - Paz-Lima, Milton Luiz da (Multi-Science Journal, 2018)
Resumo - The aim of this work was to relate the susceptibility of fruits, roots and stems of vegetables infected by P. capsici to the firmness of the pulp. The treatments were represented by 18 genotypes (carrot, papaya, chayote, apple, sweet pepper, kaki, sweet potato, gherkim, melon, tomato, Solanum gilo, potato; two genotypes of cucumber and three genotypes of pumpkim), in three replications in a delineation completely randomized designed, resulting 18*3 experimental units (EU). At the first day, with the support of a probing (tip 5 mm), the firmness of the fruits were evaluated. After that stabs of micelium of 5 mm of diameter (Pcp 42, sweet pepper) were inoculated in the wound provoked by the probing (early measured). During 7 days after the inoculating, the lesion length was evaluated, allowing the calculation of the area under the lesion progress curve (AUCPL). The incubation period was also estimated (between the inoculation and the emergence of the symptoms) and determinated the isolated pathogenicity to the genotypes in study. Cucumber (conserve and green), eggplant and sweet pepper had had the highest averages of ABCIP (F17,36=28,76**), differing statistically from the other. Tomato, gala apple and pepper had had the lowest scores of firmness (F17,36=46,81**), also differing statistically from the other. The relationship among the values of firmness and AUCPL demonstrated that as the fruit’s firmness increases the susceptibility reduces in up to 58 % (r**=-0,5796). That is the first work the relates firmness of fruits to susceptibility of P. capsici in Brazil.